Implementation of the Poisson Impedance Inversion to Improve Hydrocarbon Reservoir Characterisation in the Poseidon Field, Browse Basin, Australia - Hartagung, Riky Tri; Rosid, Mohammad Syamsu (Universitas Negeri Surabaya, 2022)
The prediction process of lithology and fluid content is the most important part of reservoir characterization. One of the methods used in this process is simultaneous seismic inversion. In the Poseidon field, Browse Basin, Australia, the parameters generated through simultaneous seismic inversion cannot accurately characterize the reservoir because of the overlapping impedance values between hydrocarbon sand, water sand, and shale, which cause a high level of ambiguity in the interpretation. The Poisson impedance (PI) inversion provides a solution to this problem by rotating the impedance a few degrees through coefficient c. Coefficient c is obtained through the target correlation coefficient analysis by finding the optimum correlation coefficient between the PI and the target log, namely, gamma rays, effective porosity, and resistivity. The results show that the PI gives better outcomes in separating hydrocarbon-saturated reservoir zones. Based on the results of the lithology impedance–gamma rays, the ϕI-effective porosity cross-plot, and the fluid impedance-water saturation (Sw) cross-plot, with optimum correlations of 0.74, 0.91, and 0.82, respectively. The lithology of hydrocarbon-saturated porous sand is at values of LI ≤ 2800 (m/s)(g*cc), ϕI ≤ 5500 (m/s)(g*cc) and FI ≤ 4000 (m/s)(g*cc). The presence of low values for LI, ϕI and FI correlates accurately with the presence of hydrocarbons in the well. Each value of c is then applied to the seismic data. The results show that this method can determine the distribution of gas-saturated porous sand on the seismic inversion section in the northeast–southwest direction.